Case Report : Pasien Laki-Laki Usia 48 Tahun dengan Sirosis Hepatis Stadium Dekompensata Relatif Hepatitis B - Najwa Zakiyya; Irwandi Irwandi (Lembaga Pengembangan Kinerja Dosen, 2025)
Liver cirrhosis is a pathological condition that describes the end stage of progressive hepatic fibrosis. More than 40% of cirrhosis patients are asymptomatic. Based on research, 4% of patients with fatty liver will develop non-alcoholic steatohepatitis, and 0.3% of these patients will end up experiencing liver cirrhosis. A 48 year old man came to the emergency room at Cut Meutia Hospital with complaints of an enlarged stomach accompanied by pain since ± 2 weeks. The patient also complained of swelling in both legs. The results of the physical examination of the abdomen revealed icteric sclera (+/+), shifting dulness and leg edema (+/+). Based on laboratory examinations, it appeared that there was an increase in liver function, then the ultrasound examination showed the impression of ascites and liver cirrhosis. Based on the history, physical examination and supporting examinations, the patient was diagnosed with hepatic cirrhosis, relative decompensated stage of hepatitis B + CHD. Non-medical management is carried out in the form of bed rest, balanced nutrition and consumption of a low sodium diet. Then the patient's medical management consists of a 500ml hepatic Aminofuscin infusion, symptomatic management and antiviral treatment for the hepatitis he is suffering from.